2017
DOI: 10.1108/raf-05-2015-0072
|View full text |Cite
|
Sign up to set email alerts
|

The profitability of Chinese banks: impacts of risk, competition and efficiency

Abstract: Purpose-This study aims to test the impacts of risk-taking behaviour, competition and cost efficiency on bank profitability in China.Design/methodology/approach-We use a two-step Generalized Method of Moments (GMM) system estimator to examine the impacts of risk, competition and cost efficiency on profitability of a sample of Chinese commercial banks over the period 2003-2013. Findings-We find that credit risk, liquidity risk, capital risk, security risk and insolvency risk significantly influence the profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
97
3
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(122 citation statements)
references
References 41 publications
13
97
3
9
Order By: Relevance
“…However, other authors pointed out that ambiguous effects depending on the profitability measure are considered (Valverde and Fernández 2007;Tan et al 2017;Trabelsi and Trad 2017), while a negative relationship between the asset structure of banks and its profitability was obtained by Bikker and Hu (2002) or Rumler and Waschiczek (2016). A large set of loans implies higher operating costs and probably the premium put on long-term interest rates (as included in the credit rate), insufficient cover for processing costs, credit losses and the cost of required capital reserves.…”
Section: Asset Compositionmentioning
confidence: 99%
“…However, other authors pointed out that ambiguous effects depending on the profitability measure are considered (Valverde and Fernández 2007;Tan et al 2017;Trabelsi and Trad 2017), while a negative relationship between the asset structure of banks and its profitability was obtained by Bikker and Hu (2002) or Rumler and Waschiczek (2016). A large set of loans implies higher operating costs and probably the premium put on long-term interest rates (as included in the credit rate), insufficient cover for processing costs, credit losses and the cost of required capital reserves.…”
Section: Asset Compositionmentioning
confidence: 99%
“…Khalid and Amjad (2012) proposed five steps for RM practices. The steps must be fully organized and followed according to the level of necessity in a non-compounded way and this in turn leads to more efficient outcomes (Tan et al, 2017). The steps are as follows:…”
Section: Ways To Measure Risk In Banksmentioning
confidence: 99%
“…Risk mostly surface in unstable environment and uncertain conditions e.g., credit risk, interest rate risk, liquidity risk, market risk, exchange risk etc. (Tan et al, 2017;Sleimi et al, 2018). This makes effective RM valuable for top management and decision makers, thus, ineffective RM could be viewed as a step toward failure (Khan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al (2016) and Djalilov and Piesse (2016) identified that the non-performing loans ratio negatively affects the profitability of banks by using a GMM approach. Similarly, Ariyadasa et al (2016) reached the same conclusion for Sri Lanka by using a vector error correction model.…”
Section: Buchory (2015) Indonesia Regressionmentioning
confidence: 99%